148: Improving Medical Students' Confidence and Interviewing Skills Regarding Adolescent Interviewing. Issue 6 (1st June 2014) - Blake, KD; Macdonald, M; Mann, K; MacCuspie, J
Abstract: BACKGROUND: The adolescent interview is a challenging task that requires strong communication skills developed through practice and training OBJECTIVES: To explore whether receiving structured feedback from an adolescent and mother Standardized Patient (SP) pair improves medical students' confidence regarding interviewing adolescents. Secondly, to identify self-perceived learning needs in the adolescent interview. DESIGN/METHODS: Participants were medical students undergoing their core Pediatric Clerkship Rotation. Students were randomized into two groups and asked to rate their confidence levels involving basic communication components of adolescent interviewing on a 13-item structured questionnaire. Following an interview with an adolescent SP and mother pair, one group received structured feedback (F1) on their performance and a second group received no structured feedback (F0). After the SP pair encounter, students were asked to rate their confidence levels a second time using the 13-item questionnaire. Students also ranked self-perceived learning needs in six components of adolescent medicine. RESULTS: Students who received structured feedback (n=25) on their adolescent interviewing skills from an SP pair showed an increase in mean confidence scores on all the 13-item structured questions. Mann-Whitney analysis comparing post-intervention confidence scores between the feedback, (F1) and no feedback (F0) groups showed that the F1 group (Mdn=27.58) had a significantly higher mean confidence score on Question 3 'Physical Exam' than did the F0 group (Mdn=17.28), U=135.50, z=−2.97, P=0.001. The F1 group (Mdn=26.14) also had a significantly higher mean confidence score on Question 6 'Sexual Issues' than the F0 group (Mdn=19.08), U=171.50, z=−1.93; P=0.023. The F1 group demonstrated a trend towards increased mean confidence scores post-intervention on questions that were directly referenced by the structured feedback tool used by the SP pair. The six ranked self-perceived learning needs indicated students felt least prepared for 'Sexuality Questioning' and most prepared for 'Physical Examination'. CONCLUSIONS: An SP interview followed by structured feedback from the SP pair improved medical students' confidence level in their adolescent interviewing skills. This study also highlighted important areas of the adolescent interview that required further training, which have since been incorporated into the undergraduate medical training at our institute. Lastly, structured feedback was shown to be a useful tool in the adolescent interview and was further incorporated into our curriculum.